A narrative review of therapies for scalp dermatomyositis. Issue 6 (30th September 2021) - Kolla, Avani M.; Liu, Lynn; Shaw, Katharina; Shapiro, Jerry; Femia, Alisa; Lo Sicco, Kristen
Abstract: Cutaneous involvement of the scalp is a common manifestation of dermatomyositis (DM), occurring in up to 82% of adults with DM. Scalp DM predominantly affects women and is characterized by dermatitis, alopecia, pruritus, and/or burning. While cutaneous DM negatively impacts quality‐of‐life, scalp symptoms in particular are often severe, debilitating, and recalcitrant to standard DM therapies. Currently, there is a paucity of guidelines to inform management of scalp symptoms in patients with cutaneous DM. In this narrative review, we summarize the treatments utilized to manage scalp DM and highlight potential areas for future research. We identified eight studies that reported on 27 treatments focused on cutaneous DM and described outcomes on scalp symptoms. A majority of the treatments were standard therapies for cutaneous DM and resulted in no or minimal improvement in scalp symptoms. Five therapies did result in complete resolution of scalp symptoms and were recommended as potential areas of future research. These included low‐dose naltrexone and platelet‐rich plasma, as well as two frequent and one less common therapy for cutaneous DM respectively: intravenous immunoglobulin, rituximab, and apremilast. Though the literature was not systematically assessed in this review, these findings illustrate not only that strategies for refractory scalp DM are lacking, but also that those demonstrating potential efficacy are limited by low levels of evidence. Additional studies, especially randomized controlled trials, are needed to better inform management of scalp DM.